Crossing the Borders of Teaching English with the Help of Band of Brothers - Imre, Attila (Acta Universitatis Sapientiae, Philologica, 2018)
The present article discusses the popularity of English since World War II, which has turned to a decisive lingua franca in Europe over the past decades and has been a major component of the thriving language industry. Our hypothesis is that when it comes to teaching foreign languages, most notably English, the inclusion of translation is rather limited (at least in Eastern Europe), and translation is even “stigmatized and excluded” from instruction (cf. Venuti 2013). However, multimedia products from the USA, most notably Hollywood movies, are highly popular among teenagers – thus, we argue for the benefits of watching (together with their scripts and subtitles) and using them as “natural” sources of language which may be used to counterbalance the textbooks and grammar books originating from the UK. We exemplify specific grammar- and vocabulary-related border crossings of institutionalized language teaching (e.g. Subject–Verb disagreement or double negative) from Band of Brothers, a highly popular TV mini-series. We also highlight the importance of the target language and individual norms when translating or subtitling taboo words. The conclusion section mentions the effectiveness of translations through subtitles, knowing that the effort is diminished when learning and entertainment is combined (cf. Caimi 2006) in the hope of serving the real needs of the learners.